Analysis of Employee Performance with Organizational Commitment as an Intervening Variable in the Surabaya City Environmental Service - Lutfy Ameilia; Akhmad Fauzi; Muhadjir Anwar (Indonesian Journal of Business Analytics, 2025)
The purpose of this study is to examine how organizational support and transformational leadership style affect worker performance at the Surabaya City Environmental Service, using organizational commitment as an intervening variable.  This study employs a survey method in conjunction with a quantitative approach.  Questionnaires were distributed to respondents who work for the Surabaya City Environmental Service in order to gather data.  With the use of SmartPLS software, structural equation modeling, or SEM, is the data analysis method employed.  According to the study's findings, (1) employee performance is not significantly impacted directly by transformational leadership, (2) employee performance is significantly positively impacted by organizational support, (3) organizational commitment can significantly mediate the impact of transformational leadership on employee performance, and (4) organizational commitment also significantly mediates the impact of organizational support on employee performance.  These results highlight how crucial organizational commitment is to raising employee performance through positive interactions among individuals, organizations, and leaders.